75.4k views
0 votes
How do I differentiate the function f(x)=(-2x^3+1)^5 with respect to x?

User Ironsun
by
4.6k points

1 Answer

0 votes

To solve this problem, we're going to have to use the chain rule. Let
g(x)=x^5 \text{ and } h(x)=-2x^3+1

f(x)=g(h(x)) which means that g(x)'s input changes at a different speed than x and that speed is the derivative of h(x). Written down, since it seems kinda weird to explain, we have:


(df(x))/(dx)=(dg(x))/(dh(x))*(dh(x))/(dx)

so that mean's we're analyzing:


f'(x)=g'(h(x)))h'(x)

So:
5(-2x^3+1)^4*(-6x^2)=-480 x^(14) + 960 x^(11) - 720 x^(8) + 240 x^(5) - 30 x^2

User Romulus
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.